Chilka - Ahmed,Urooj (Bookgroup Karachi, 2023)
Chilka" is a poem that celebrates the often-overlooked skins of fruits and vegetables. Through vivid imagery and evocative language, the poem explores the beauty and significance of these natural coverings. The peel of fruits and vegetables is described in a way that highlights its texture, color, and role, turning these everyday elements into objects of poetic appreciation.